MINOL (ALCOHOLIC BEVERAGE) Bill IN THE TIME OF THE COVID-19 PANDEMIC IN PERSPECTIVE LAW AND HAM - Daniel Gombo, Putu (Ganesha Law Review, 2021)
This study aims to analyze the Covid-19 pandemic Minol (Alcoholic Drinks) Prohibition Bill from a legal and human rights perspective and review the draft Law on the Prohibition of Minol (Alcoholic Drinks). This research is a research that uses normative legal research methods using the invitation approach (statue approach). This normative study was conducted by collecting primary, secondary and tresier legal materials. The material collected is then arranged systematically and analyzed using descriptive qualitative methods. The results of this study indicate that the existence of the Bill or Bill on the Prohibition of Minol (Alcoholic Drinks) is one of the things that threatens legal human rights (the right to legal equality) for alcoholic drink lovers and some residents who do not have a source of water that makes drinks. alcoholic as a water appearance. The Bill or Draft Bill on the Prohibition of Minol (Alcoholic Drinks), which is being drafted in the discussion at the House of Representatives, has triggered a trigger for crime in Indonesia.